Simultaneous “traumatic Gerbode” and aortic rupture due to blunt chest trauma - Anninos, Hector (Ann Card Anaesth, 2016)
The Gerbode defect is characterized by a perimembranous ventricular septal defect between the left ventricle and the right atrium. This intracardiac shunt is a congenital defect but may be iatrogenic after valve surgery or atrioventricular node ablation, may be the result of endocarditis or may be traumatic. It is really rarely encountered as sequelae of non-penetrating heart trauma, and their clinical manifestations may often be unrecognized in the multi-injured patient. However, they are serious complications, and their diagnostic approach is not always feasible. We hereby present a case of a young man with the left ventricle to the right atrium communication after blunt thoracic trauma due to a car accident and concomitant rupture of the thoracic aorta. We present also the case and the ways of treatment according to the international bibliography.